PRACTICAL ASPECTS OF CREATING COST ESTIMATE IN BUDGET ORGANIZATIONS - Norkochkarov, Abdulaziz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article presents a description of the research conducted on the improvement of the procedure for drawing up and approving estimates in budget organizations. The need to prepare and approve estimates in budget organizations is theoretically based. In it, research was carried out to identify existing problems by analyzing the current state of budget organizations' preparation and approval procedure. Scientific and practical proposals and recommendations on improving the procedure for drawing up estimates in budget organizations are given.